2013
DOI: 10.1097/pec.0b013e31829e7d6a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Examination in Establishing the Diagnosis of Pneumonia

Abstract: Results demonstrate the significant added value of chest radiography as an ancillary test for diagnosis of pneumonia in the emergency department setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
1
19
0
2
Order By: Relevance
“…GBS pneumonia mimics RDS,25 and should be considered if a baby with radiographic appearances of RDS, is disproportionately sick. NICE guidelines5 do not give a directive on the role of chest radiography as part of a screen for EONS, however, it is notable that even in older children pneumonia may be present with limited clinical signs, and there is significant added value of chest radiography in the diagnosis of pneumonia 26…”
Section: The Role Of Chest Radiographmentioning
confidence: 99%
“…GBS pneumonia mimics RDS,25 and should be considered if a baby with radiographic appearances of RDS, is disproportionately sick. NICE guidelines5 do not give a directive on the role of chest radiography as part of a screen for EONS, however, it is notable that even in older children pneumonia may be present with limited clinical signs, and there is significant added value of chest radiography in the diagnosis of pneumonia 26…”
Section: The Role Of Chest Radiographmentioning
confidence: 99%
“…Based on study selection criteria, 1 Class II study 41 and 8 Class III studies [42][43][44][45][46][47][48][49] were included to answer this critical question.…”
Section: For Wellmentioning
confidence: 99%
“…Oxygen saturation has been shown to be lower in subjects with radiographic pneumonia in 4 Class III studies; however, these studies did not agree on a specific cutoff value. [45][46][47][48] In a study by Simon et al, 45 hypoxia was found to be predictive of radiographic pneumonia but had inadequate sensitivity and specificity to recommend a specific cutoff value for oxygen saturation; in fact, radiographic pneumonia was found in half of patients with an oxygen saturation of 96% or higher. Therefore, the absence of hypoxia in their study group did not rule out radiographic pneumonia.…”
Section: For Wellmentioning
confidence: 99%
“…Despite frequent use of X-ray in clinical settings, there are still debates regarding its necessity in patients suspected of having CAP. In this regard, Ayalon et al investigated the role of physical examination in the diagnosis of pneumonia and demonstrated the significant benefit of CXR as an ancillary test for the diagnosis of pneumonia in ED settings (7). In addition, according to a review published in 2003, CXR was considered as the gold standard for diagnosing pneumonia.…”
Section: Introductionmentioning
confidence: 99%